PROFILE OF STUDENTS' NUMERACY LITERACY ABILITY AND SELF EFFICACY IN MATHEMATICS LEARNING - Zulfayani, Zulfayani; Ariawan, Rezi; Nufus, Hayatun; Kafrina, Kafrina (Mathematics Research and Education Journal, 2023)
This study aims to describe the ability of numeracy literacy and mathematical self-efficacy of students in learning mathematics. This research is a descriptive study with a quantitative approach conducted at SMPN 34. The research instruments used are numeracy literacy test questions and self-efficacy questionnaires that have met the criteria for good instrument feasibility. The data analysis technique used is Descriptive Analysis. The results showed that overall the numeracy literacy skills of the students included in the criteria were not good. There are 73.30% or 20 people of the total number of students who have not been able to solve the numeracy literacy test questions correctly. Furthermore, the overall mathematical self-efficacy of students is included in the moderate criteria with a percentage of 70% or 21 students. Next for numeracy literacy skills in terms of mathematical self-efficacy (high, medium, and low), each has different numeracy literacy skills. Students whose self-efficacy is high, have good numeracy literacy skills, while students whose self-efficacy is moderate and low, have poor numeracy literacy skills. From the results of this study, it is necessary to research to improve the numeracy literacy skills and mathematical self-efficacy of students at SMPN 34 Pekanbaru.